2006
DOI: 10.1111/j.2042-3306.2006.tb05528.x
|View full text |Cite
|
Sign up to set email alerts
|

Racing speeds of Quarter Horses, Thoroughbreds and Arabians

Abstract: This study demonstrates that Quarter Horses achieve faster racing speeds than do other breeds. It also reveals a potential flaw in race-riding strategy as a more consistent pace throughout the Arabian and longer Thoroughbred races may be more efficient and result in a faster overall race time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 4 publications
0
19
1
1
Order By: Relevance
“…horse behaviour). This was not seen in QH races, and this may be because QHs race over shorter distances [11] and at greater speeds [12] than TBs, and that falls under these circumstances, regardless of cause, have a greater likelihood of resulting in injury to the jockey. With an additional year's data, this result is in agreement with the group's previous study [1].…”
Section: Discussionmentioning
confidence: 84%
“…horse behaviour). This was not seen in QH races, and this may be because QHs race over shorter distances [11] and at greater speeds [12] than TBs, and that falls under these circumstances, regardless of cause, have a greater likelihood of resulting in injury to the jockey. With an additional year's data, this result is in agreement with the group's previous study [1].…”
Section: Discussionmentioning
confidence: 84%
“…In the study reported here, some breeds were associated with an increased risk of elimination, compared with that of purebred Arabians (Table 1). Previous studies 18,19 have found physiologic differences between Arabians and other breeds during race training. However, clinical data from endurance competition have not been previously evaluated to identify breeds at risk.…”
Section: Discussionmentioning
confidence: 95%
“…There was increased severity of disease recognised in Quarter Horses with regards to both the number of bones affected and the grade of articular cartilage damage. This may in part be due to the higher speeds achieved by Quarter Horses during racing compared with Thoroughbreds resulting in increased concussive loads. It is a personal observation of C.W.M.…”
Section: Discussionmentioning
confidence: 99%